THE USE OF INNOVATIVE METHODS IN THE COURSE OF THE LESSON (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Innovation has revolutionized the education landscape by introducing dynamic and engaging methods into traditional lessons. This article explores the significance of using innovative methods in teaching, the benefits they offer, and examples of how educators can incorporate them to create impactful learning experiences